Compensation And Workplace Behaviour: The Catalysts For Personnel Job Performance In Ministries Of Education In North- Central Geo-Political Zone, Nigeria - AYINDE, Yusuf Adisa (International Journal of Educational Management, 2025)
This study examined the relationship among compensation, workplace behaviour and personnel job performance in Ministries of Education in North Central States, Nigeria. The objectives of the study were to: (i) examine the level of staff compensation; (ii) investigate the level of workplace behaviour; (iii) examine the level of personnel job performance; and (iv) examine the relationship among compensation, workplace behaviour and personnel job performance. The study was a descriptive research design of correlation type. Multi-stage sampling technique was used for the study. Three states were randomly selected out of the six States in the Geo-political Zone. Purposive sampling technique was used to select all the three States Ministries of Education in these States. Random sampling technique was used to select 503 staff out of the 878 staff in the States ministries of education, and 145 principal officials (Directors, Assistant and Deputy Directors) out of the 243 in the states which constituted 60%. "Compensation Questionnaire" (CQ), Workplace Behaviour Questionnaire" (WPO and "Personnel Job Performance Questionnaire" (P JPQ) were used to collect data for the study. The instruments were validated by the experts and also tested for reliability. The reliability coefficients for CQ, WPQ and PJPQ were 0.67, 0.75 and 0.86 respectively. Research questions were answered using Mean and Standard Deviation while Multiple Regression and Pearson Product Moment Correlation were used to test main and operational hypotheses at .05 alpha level. Thus, the study concluded that effective compensation and efficient workplace behavior play significant roles in enhancing personnel job performance which would consequently facilitate realisation of institutional goals in Ministries of Education in North Central States, Nigeria. Based on the findings and conclusion, the study recommended that, state governments should intensify their efforts by paying more attention to staff compensation through prompt payment of attractive salary, timely promotion, provision of affordable health services and improved training opportunities and also ensure that staff maintain workplace behaviour through strict implementation of staff code of conduct and ensure that appropriate sanctions are carried out on defaulters.